Training On Calculation Of Cost Of Goods Products In The Home Industry Of Gemah Village, Semarang - Nurchayati; C Sri Haryanti; Parju; Rr Suprantiningrum (International Journal of Community Engagement and Development, 2024)
The purpose of the product cost calculation training is to provide in-depth knowledge for home industry business actors in Gemah Village, Semarang in order to improve their business efficiency and sustainability. The method used in this training is an interactive workshop which includes basic discussion of production costs, identification of cost components, analysis of product cost calculation and interactive discussion and question and answer. The costs that affect COGS can be correctly identified through the calculation of the cost of goods because during its business this household industry has not included elements of direct labor costs, factory overhead costs, administrative and general costs and marketing costs, as a result the sales results obtained are too low. By using the full cost method, the cost of goods can be determined precisely so that business actors get the right seller results. With this training, it is hoped that household industries in Gemah Village, Semarang can determine the right selling price so that they can get decent profits and can be competitive.